2009
DOI: 10.2337/dc09-1227
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of A1C and Fasting Glucose Criteria to Diagnose Diabetes Among U.S. Adults

Abstract: OBJECTIVETo compare A1C and fasting glucose for the diagnosis of diabetes among U.S. adults.RESEARCH DESIGN AND METHODSThis study included 6,890 adults (≥20 years of age) from the 1999–2006 National Health and Nutrition Examination Survey without a self-reported history of diabetes who had fasted ≥9 h. A1C ≥6.5% and fasting glucose ≥126 mg/dl were used, separately, to define diabetes.RESULTSOverall, 1.8% of U.S. adults had A1C ≥6.5% and fasting glucose ≥126 mg/dl, 0.5% had A1C ≥6.5% and fasting glucose <126 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
107
8
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(144 citation statements)
references
References 7 publications
(11 reference statements)
22
107
8
2
Order By: Relevance
“…Another analysis on 6890 adults without previouslydiagnosed diabetes from the 1999 -2006 NHANES study showed a reasonable consistency between HbA 1c and fasting glucose measurements for the purposes of diagnosing diabetes (k = 0.60; 95% CI 0.55, 0.64), although discrepancies were reported for non-Hispanic black patients [ 51 ].…”
Section: Hba 1c For Diagnosis and Monitoring Backgroundmentioning
confidence: 99%
“…Another analysis on 6890 adults without previouslydiagnosed diabetes from the 1999 -2006 NHANES study showed a reasonable consistency between HbA 1c and fasting glucose measurements for the purposes of diagnosing diabetes (k = 0.60; 95% CI 0.55, 0.64), although discrepancies were reported for non-Hispanic black patients [ 51 ].…”
Section: Hba 1c For Diagnosis and Monitoring Backgroundmentioning
confidence: 99%
“…This is because the current criteria adopted show a discrepancy between the proportion and profile of patients identified as having DM by the A1C, compared to the tests based on glycemia (45,46). In addition, the patients who present special conditions that interfere with A1C results should be screened for DM with alternative markers.…”
Section: Ga In the Diagnosis Of Dmmentioning
confidence: 99%
“…98 using NHANES data, with cut-off levels of 6.5% for HbA 1c and 7.0 mmol/l for FPG. There was some disagreement between the tests, but 96% were not diagnosed as diabetic by both, and 1.8% were diagnosed as diabetic by both.…”
Section: Suggested Conclusionmentioning
confidence: 99%